A análise da representação gráfica de projetos civis com CAD, BIM E RA para identificar as interferências de obra em projetos complementares - Martins, Lucas Francisco (2018)
Since the beginning of the technical graphical representation, there are problems in reducing the dimensionality of 3D for 2D. The projects in AEC (Architecture, Engineering and Construction) adopt the paradigm of top view or orthogonal projection in 2D. This type of pattern lasted until CAD (Computer Aided Design). Two important changes in the technical representation of the projects were, the change in the 3D perspective view of the role for virtual 3D and in the interactions with the new technological platforms RA (augmented reality) and BIM (Building Model Information). In AEC projects, there are problems of incompatibility or interference, classified into three types: hard clash, soft clash and 4D clash. In this context, the research problem is the improvement of the visualization and identification of the interferences of the project for engineers and architects, face of the technologies of representation, CAD, BIM and RA. The hypothesis of this work is that 3D vision improves the identification of interferences in the design, and that the hit rate improves with changing the visual variable color tone pattern, helping the user in the identification of direct interferences. It is proposed the UCD (User Centered Design) approach, using the questionnaire method and a protocol of effectiveness tests for the understanding of aspects of user perception in the use of common tools in the compatibilization of projects. The aim of this research is to evaluate how the differences between the 2D environment and the 3D influence the effectiveness of cartographic communication on civil projects, identifying possible advantages of BIM and RA for the visualization and compatibilization of complementary projects.